A rapid systematic review: effects of Covid-19 on mental health and well-being of the university students - Min, Myat; Zaw, Cho Cho (SAS Publishers, 2022)
Introduction: The impact of coronavirus disease 2019 (COVID-19) among the University students as a vulnerable population is essential to be highlighted. This study aimed to identify the effects of Covid-19 on mental health and well-being of the university students. Methods: A rapid systematic review was used to explore all the available and reliable sources from three main databases and grey literature sources in April and May 2022. It included all studies about mental health related problems among university students delivered in response to the COVID-19 pandemic. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) flow chart was used. Scoups list April 2022 of published journals was also viewed to verify the validity of literature. Results: A total of 4773 articles were retrieved from three databases through BMC, PMC and Science Direct and 50 articles from other sources. Among them, 32 studies were chosen for review after excluding the articles which were not directly related, non-full text, non-Scopus, and duplicates. Conclusion: Three major themes focused on university students: (a) factors involved in psychological impact and well-being of the students, (b) prevalence of mental health issues during Covid-19 pandemic, and (c) Coping strategies in dealing with the effects of Covid-19 were developed. The findings from the study are expected to provide a source of knowledge sharing and improving strategies for the students, educators, counsellors, management, and the policy makers.